Pasts at play childhood encounters with history in British culture 1750 - 1914 - Davies, Rachel Bryant; Gribling, Barbara (Manchester University Press, 2020)
Pasts at play showcases a range of approaches to children's literature and culture, from disciplines including Classics, English Literature, and History. The ten essays integrate visual and material culture into historical practice to analyse how nineteenth-century children interacted playfully with the past to generate moral lessons.
Keywords: Children's literature, English -- History and criticism.; Children.; Littérature de jeunesse anglaise -- Histoire et critique.; LITERARY CRITICISM / General; Children; Children's literature, English; børne- og ungdomslitteratur.; bsup.; Criticism, interpretation, etc.